Environmental health risk assessment of urban water sources based on fuzzy set theory - Liao Di; Jin Yongsheng; Zhang Xiao (Open Geosciences, 2023)
Water pollution and protection of water resources have become an urgent task for humanity today and are also important components of environmental risk assessment. In response to the problems of high risk level and low risk credibility in the current environmental health risk assessment of urban water sources, this article aims to use fuzzy set theory to comprehensively evaluate the environmental quality and quickly monitor the safety of urban water sources. Therefore, this article analyzed the health factors of the urban water source environment and then studied the content and uncertainty analysis of health risk assessment. Finally, it constructed a health risk assessment system and proposed corresponding water environment protection strategies. In the experimental section, the risk level and risk credibility of the water environment were analyzed. Through comparison, it was found that the risk level in the new water environment health risk assessment was 0.16 lower than that in the traditional water environment health risk assessment, and the risk credibility was 0.11 higher than that in the traditional water environment health risk assessment. The water quality monitoring effect in the new water environment health risk assessment was 7.3% higher than that in the traditional water environment health risk assessment, The health hazard effect is 8.2% lower than traditional water environment health risk assessment. In summary, water environment health risk assessment plays an important role in protecting the water source environment. Health risk assessment of the water environment helps to reduce water pollution, improve water quality, and ultimately improve human health. Moreover, using fuzzy set theory makes it easier to comprehensively and efficiently evaluate the water environment. The innovation of this article lies in paying attention to the importance of fuzzy set theory in water pollution risk assessment and applying fuzzy technology to water pollution control strategies, to better improve water quality and optimize water source environmental health risk assessment methods.